Optimal Technologies for External Thermal Insulation with Polystyrene Panels for Different Support Materials. (2015) - Bojan, Adrian; Aciu, Claudiu
Abstract: In the context of the energy crisis and environmental degradation, a particular importance has the reduction of operational energy in buildings by the reduction of heat losses through exterior walls. The thermal insulation of buildings leads to operational energy savings, contributing to the reduction of environmental pollution due to current energy production systems. Given the importance of energy savings and material costs, the paper presents optimal technologies for polystyrene board thermal insulation applied on different substrates. By developing these technologies for energy saving and cost reduction, the paper falls in the category of sustainable development technologies.